Blood Biochemical Profile, Growth Performance, Carcass Characteristics and Meat Quality of Mallard and Muscovy Ducks Fed Diet Supplemented with Bay Leaves (Syzygium polyanthum) - Ismoyowati; Indrasanti, Diana; Sumarmono, Juni (International Journal of Poultry Science, 2015)
The purpose of this experiment was to investigate the interaction effect between genetic and bay leaf supplementation in the diet on blood biochemical profile, growth performance, carcass characteristics and meat quality of local Mallard and Muscovy ducks. A total of 128 (64 of each breed) day old male ducks were utilized for the study. The experimental design was completely randomized in a factorial pattern. The first factor was breed of duck (Mallard and Muscovy) and the second factor was bay leaf supplementation in the diet at various levels (0%-control, 3, 6 and 9%. The breed type had highly significant (p<0.01) effect on blood biochemistry profile viz. plasma proteins, uric acid, glucose, triglycerides, cholesterol, LDL and HDL. Mallard ducks showed higher (p<0.05) values for all these parameters than Muscovy ducks, except blood glucose level. The results showed that 3% bay leaves in the diet were able to reduce the uric acid content of Mallard ducks up to 6.71±3.44 mg/dl compared to 19.47±4.5 in the control group. In Muscovy ducks, 6% bay leaves supplementation caused the largest decline in uric acid content up to 2.14±1.29 mg/dl compared to 4.66±1.29 mg/dl in the control group. Breed of ducks had highly significant effects (p<0.01) on growth rate, carcass weight, dressing percentage and meat fat content. Muscovy outperformed mallard ducks in term of growth rate, carcass weight and dressing percentage; however, total meat fat was found to be significantly (p<0.05) lower in Mallard ducks. Bay leaves supplementation up to 9% did not interfere with growth performance, carcass weight and dressing percentage of both Mallard and Muscovy ducks. There was a significant (p<0.05) effect on meat fat and cholesterol between the groups fed bay leaves in the diet and control group, with lowest values in group supplemented with 9% bay leaves in the diet in both Muscovy and Mallard ducks. In conclusion, the supplementation of bay leaves resulted in reduction of meat fat and cholesterol of ducks, thus could prove as a viable for health conscious people.